Adhesive composition, laminate, packaging material, and packaging material for battery case
By using an adhesive composition including a crystalline modified olefin polymer, an anhydride monomer and a crosslinking agent, the problems of insufficient adhesion and poor heat resistance during low-temperature lamination are solved, and a packaging material with high adhesion and good heat resistance are achieved.
Patent Information
- Application Number
- CN202380054896.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-07
AI Technical Summary
The existing adhesives are insufficient adhesion and poor heat resistance during low-temperature lamination, making it difficult to meet the dual requirements of lithium battery packaging materials for adhesion and heat resistance.
Adhesiveness and heat resistance are improved by crosslinking reactions using an adhesive composition containing crystalline modified olefin polymer, anhydride monomer and a crosslinking agent.
It achieves high adhesion and good heat resistance during low-temperature lamination, and is suitable for the manufacture of lithium battery packaging materials.
Smart Images

Figure CN119585390A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition, a laminate, a packaging material, and a battery case packaging material, and more particularly to an adhesive composition, a laminate having an adhesive layer formed from the adhesive composition, a packaging material having the laminate, and a battery case packaging material having the packaging material. Background Art
[0002] In recent years, lithium batteries have been used as batteries used in personal computers, mobile terminal devices, etc. from the viewpoint of reducing thickness. In addition, lithium batteries are sealed with, for example, a packaging material.
[0003] Such a packaging material can be obtained by, for example, bonding an aluminum foil layer and a polypropylene film with an adhesive.
[0004] As such an adhesive, for example, an adhesive composition containing a maleic anhydride-modified propylene-butene copolymer, an epoxy resin, and 1,2,3,6-tetrahydrophthalic anhydride has been proposed (for example, see Example 10 of Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 030050 Pamphlet Summary of the invention
[0008] Problems to be solved by the invention
[0009] On the other hand, such adhesives are required to have good adhesion during low-temperature lamination from the viewpoint of improving productivity.
[0010] In addition, such an adhesive is also required to have heat resistance.
[0011] The present invention provides an adhesive composition having excellent adhesion and heat resistance during low-temperature lamination, a laminate having an adhesive layer formed of the adhesive composition, a packaging material having the laminate, and a battery case packaging material having the packaging material.
[0012] Means for solving problems
[0013] The present invention [1] is an adhesive composition comprising a crystalline modified olefin polymer, an acid anhydride monomer, and a crosslinking agent, wherein the crystalline modified olefin polymer is a crystalline α-olefin polymer having 2 to 20 carbon atoms modified by a monomer having a functional group capable of reacting with an epoxy group or an oxazoline group, the acid anhydride monomer has a ring structure and two or more acid anhydride groups, and the crosslinking agent comprises an epoxy compound and / or an oxazoline compound.
[0014] The present invention [2] includes the adhesive composition described in [1] above, further comprising a non-crystalline hydrocarbon polymer having a dynamic viscosity at 200° C. of 1 cSt to 100,000 cSt.
[0015] The present invention [3] includes the adhesive composition described in [2] above, wherein the non-crystalline hydrocarbon polymer is a polymer of an olefin having 2 to 20 carbon atoms.
[0016] The present invention [4] includes the adhesive composition according to any one of the above [1] to [3], further comprising a catalyst.
[0017] The present invention [5] includes the adhesive composition described in the above [4], wherein the catalyst is an amine catalyst.
[0018] The present invention [6] includes the adhesive composition according to any one of [1] to [5] above, wherein the functional group is an acid anhydride group.
[0019] The present invention [7] includes a laminate comprising, on one side in the thickness direction, a first adhesive layer formed from the adhesive composition according to any one of the above [1] to [6] and a substrate in this order.
[0020] The present invention [8] includes a packaging material comprising an inner layer and the laminate described in [7] in this order on one side in the thickness direction.
[0021] The present invention [9] includes a battery case packaging material comprising the packaging material described in [8] above, a second adhesive layer, and an outer layer in this order on one side in the thickness direction.
[0022] Effects of the Invention
[0023] The adhesive composition of the present invention comprises a crystalline modified olefin polymer, an acid anhydride monomer, and a crosslinking agent. In such an adhesive composition, the crystalline modified olefin polymer, the acid anhydride monomer, and the crosslinking agent undergo a crosslinking reaction to be cured.
[0024] Furthermore, the anhydride monomer has two or more anhydride groups. Therefore, in the cross-linking reaction, the cross-linking density is increased. As a result, the adhesion during low-temperature lamination is improved.
[0025] In addition, the acid anhydride monomer has a ring structure, and as a result, heat resistance is improved.
[0026] The laminate of the present invention comprises a first adhesive layer formed from the adhesive composition of the present invention, and therefore has excellent adhesion and heat resistance during low-temperature lamination.
[0027] The packaging material of the present invention comprises the laminate of the present invention and therefore has excellent adhesion and heat resistance during low-temperature lamination.
[0028] The battery case packaging material of the present invention comprises the packaging material of the present invention, and therefore has excellent adhesion and heat resistance during low-temperature lamination. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] [ Figure 1 ] Figure 1 This is a schematic diagram showing one embodiment of the laminated body of the present invention.
[0030] [ Figure 2 ] Figure 2 A and Figure 2 B shows one embodiment of the method for producing a laminated body of the present invention. Figure 2 A shows the first step of preparing a substrate. Figure 2 B shows the second step of arranging (forming) the first adhesive layer on the other surface in the thickness direction of the substrate.
[0031] [ Figure 3 ] Figure 3 This is a schematic diagram showing one embodiment of the packaging material of the present invention.
[0032] [ Figure 4 ] Figure 4 This is a schematic diagram showing one embodiment of the battery case packaging material of the present invention and a battery using the battery case packaging material. DETAILED DESCRIPTION
[0033] 1. Adhesive composition
[0034] The adhesive composition contains a crystalline modified olefin polymer, an acid anhydride monomer, and a crosslinking agent.
[0035] <Crystalline modified olefin polymer>
[0036] The crystalline modified olefin polymer is a crystalline α-olefin polymer having 2 to 20 carbon atoms modified with a monomer having a functional group reactive with an epoxy group or an oxazoline group.
[0037] [Crystalline α-olefin polymer having 2 to 20 carbon atoms]
[0038] The crystalline α-olefin polymer having 2 to 20 carbon atoms is an olefin polymer containing a structural unit derived from an α-olefin having 2 to 20 carbon atoms that can form a crystalline polymer. That is, the crystalline α-olefin polymer having 2 to 20 carbon atoms is formed by polymerizing an α-olefin having 2 to 20 carbon atoms. It should be noted that the so-called crystallinity is defined as a property of a compound having a heat of fusion (described later) of 1 J / g or more.
[0039] Examples of the α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.
[0040] As the structural unit derived from an α-olefin having 2 to 20 carbon atoms, preferably, there can be mentioned a structural unit derived from an α-olefin having 2 to 4 carbon atoms. As the structural unit derived from an α-olefin having 2 to 20 carbon atoms, more preferably, there can be mentioned a structural unit derived from propylene and a structural unit derived from 1-butene. That is, the crystalline α-olefin polymer having 2 to 20 carbon atoms is preferably a propylene / 1-butene copolymer.
[0041] The type and content ratio of the structural unit derived from the α-olefin having 2 to 20 carbon atoms are selected so that the olefin polymer becomes crystalline.
[0042] Specifically, when the structural unit derived from an α-olefin having 2 to 20 carbon atoms includes a structural unit derived from propylene and a structural unit derived from 1-butene, the content ratio of the structural unit derived from propylene is, for example, 50 mol% or more, preferably 60 mol% or more, and for example, 95 mol% or less, preferably 85 mol% or less, relative to 100 mol% of the total amount of the structural unit derived from propylene and the structural unit derived from 1-butene. In addition, the content ratio of the structural unit derived from 1-butene is, for example, 5 mol% or more, preferably 15 mol% or more, and for example, 50 mol% or less, preferably 40 mol% or less, relative to 100 mol% of the total amount of the structural unit derived from propylene and the structural unit derived from 1-butene.
[0043] When the content ratio of the structural unit derived from propylene and the content ratio of the structural unit derived from 1-butene are not less than the above lower limit and not more than the above upper limit, the adhesiveness during low-temperature lamination is excellent.
[0044] It should be noted that the above-mentioned content ratio can be obtained by, for example 13 The results were confirmed by known means such as C-NMR measurement (the same applies hereinafter).
[0045] The crystalline α-olefin polymer having 2 to 20 carbon atoms can be obtained by the method described in, for example, Japanese Patent No. 3939464 and International Publication No. 2004 / 87775. Specifically, the crystalline α-olefin polymer having 2 to 20 carbon atoms can be obtained by polymerizing an α-olefin having 2 to 20 carbon atoms in the presence of a metallocene catalyst.
[0046] The heat of fusion of the crystalline α-olefin polymer having 2 to 20 carbon atoms measured in accordance with JIS K7122 is, for example, 1 J / g or more, preferably 10 J / g or more, more preferably 20 J / g or more, and, for example, 50 J / g or less, preferably 40 J / g or less.
[0047] When the heat of fusion is not less than the above lower limit and not more than the above upper limit, the adhesiveness during low-temperature lamination is excellent.
[0048] The melting point of the crystalline α-olefin polymer having 2 to 20 carbon atoms is, for example, 40° C. or higher, preferably 60° C. or higher, and, for example, 100° C. or lower, preferably 90° C. or lower.
[0049] In addition, the melting point can be measured using a differential scanning calorimeter (the same applies hereinafter).
[0050] The weight average molecular weight of the crystalline α-olefin polymer having 2 to 20 carbon atoms measured by GPC (gel permeation chromatography) and calculated in terms of standard polystyrene is, for example, 10,000 or more, preferably 50,000 or more, and, for example, 500,000 or less, preferably 400,000 or less.
[0051] The crystalline α-olefin polymer having 2 to 20 carbon atoms may be used alone or in combination of two or more.
[0052] [monomer]
[0053] The monomer has a functional group capable of reacting with an epoxy group or an oxazoline group.
[0054] Examples of such a functional group include a hydroxyl group, an amino group, a carboxyl group, an acid anhydride group, an ester group, and a thiol group.
[0055] The monomer is a compound having the above-mentioned functional group, for example, ethylenically unsaturated compounds containing a hydroxyl group, ethylenically unsaturated compounds containing an amino group, unsaturated carboxylic acids, unsaturated carboxylic anhydrides, vinyl ester compounds, and ethylenically unsaturated compounds containing a thiol group.
[0056] The ethylenically unsaturated compound containing a hydroxyl group has a hydroxyl group as the functional group. As the ethylenically unsaturated compound containing a hydroxyl group, for example, a (meth)acrylate containing a hydroxyl group can be cited. As the (meth)acrylate containing a hydroxyl group, for example, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate can be cited.
[0057] The amino group-containing ethylenically unsaturated compound has an amino group as the functional group. Examples of the amino group-containing ethylenically unsaturated compound include aminomethyl (meth)acrylate and propylaminoethyl (meth)acrylate.
[0058] The unsaturated carboxylic acid has a carboxyl group as the functional group. Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.
[0059] The unsaturated carboxylic anhydride has an acid anhydride group as the functional group. Examples of the unsaturated carboxylic anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride. Preferably, maleic anhydride is used as the unsaturated carboxylic anhydride.
[0060] The vinyl ester compound has an ester group as the functional group. Examples of the vinyl ester compound include vinyl acetate, vinyl propionate, and vinyl n-butyrate.
[0061] The thiol group-containing ethylenically unsaturated compound has a thiol group as the functional group. Examples of the thiol group-containing ethylenically unsaturated compound include allyl mercaptan and 2-vinylbenzyl mercaptan.
[0062] As the monomer, preferably unsaturated carboxylic acid and / or unsaturated carboxylic anhydride can be mentioned. That is, as the above-mentioned functional group, preferably carboxyl and / or anhydride group can be mentioned. If the functional group is carboxyl and / or anhydride group, it can improve the application period and the adhesion during low temperature lamination.
[0063] In addition, as a monomer, unsaturated carboxylic anhydride is more preferably mentioned. That is, as the above-mentioned functional group, an acid anhydride group is more preferably mentioned. If the functional group is an acid anhydride group, the pot life and the adhesion during low-temperature lamination can be further improved.
[0064] The monomers may be used alone or in combination of two or more.
[0065] [Production of Crystalline Modified Olefin Polymer]
[0066] The crystalline modified olefin polymer can be obtained by modifying a crystalline α-olefin polymer having 2 to 20 carbon atoms with a monomer.
[0067] In order to modify a crystalline α-olefin polymer having 2 to 20 carbon atoms with a monomer, for example, first, the crystalline α-olefin polymer having 2 to 20 carbon atoms is dissolved in a known organic solvent (for example, toluene).
[0068] Next, monomers and a radical polymerization initiator are added, and the mixture is heated and stirred.
[0069] The modification amount (introduction amount) of the monomer in the modified product of the crystalline α-olefin polymer having 2 to 20 carbon atoms, that is, the content ratio of the structural unit derived from the monomer in the modified product of the crystalline α-olefin polymer having 2 to 20 carbon atoms, is, for example, 0.1 mass % or more, preferably 0.5 mass % or more, and is, for example, 15 mass % or less, preferably 10 mass % or less, more preferably 5 mass % or less, further preferably 4 mass % or less, particularly preferably 2 mass % or less, and most preferably 1.5 mass % or less.
[0070] When the modification amount is not less than the above lower limit and not more than the above upper limit, the pot life can be increased.
[0071] The above modification amount can be determined by, for example 1 The results can be confirmed by known means such as H-NMR measurement.
[0072] Examples of the radical polymerization initiator include organic peroxides and organic peresters.
[0073] Examples of the organic peroxide include diisopropylbenzene peroxide, benzoyl peroxide, dichlorobenzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)hex-3-yne, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and tert-butyl peroxybenzoate. Examples of the organic perester include tert-butyl peroxyacetate, tert-butyl peroxyphenylacetate, tert-butyl peroxyisobutyrate, tert-butyl peroxysec-octanoate, tert-butyl peroxypivalate, cumyl peroxypivalate, and tert-butyl peroxydiethylacetate.
[0074] As the radical polymerization initiator, preferably, an organic peroxide is used, and as the radical polymerization initiator, more preferably, di-tert-butyl peroxide is used.
[0075] The blending ratio of the radical polymerization initiator is, for example, 0.001 parts by mass or more, and for example, 10 parts by mass or less, relative to 100 parts by mass of the crystalline α-olefin polymer having 2 to 20 carbon atoms.
[0076] The radical polymerization initiator can be used alone or in combination of two or more.
[0077] The heating temperature is, for example, 50° C. or higher, preferably 80° C. or higher, and for example, 250° C. or lower. The reaction time is, for example, 1 minute or longer, and for example, 10 hours or shorter.
[0078] Thus, a crystalline α-olefin polymer having 2 to 20 carbon atoms is modified with a monomer to obtain a crystalline modified olefin polymer (a varnish of a crystalline modified olefin polymer).
[0079] The melting point of the crystalline modified olefin polymer is, for example, 40° C. or higher, preferably 60° C. or higher, and, for example, 100° C. or lower, preferably 90° C. or lower.
[0080] The crystalline modified olefin polymer has a weight average molecular weight in terms of standard polystyrene as measured by GPC, for example, 10,000 or more, preferably 50,000 or more, and for example, 500,000 or less, preferably 300,000 or less, and more preferably 200,000 or less.
[0081] The content ratio of the crystalline modified olefin polymer will be described later.
[0082] <Anhydride Monomer>
[0083] The acid anhydride monomer has a ring structure and two or more acid anhydride groups. The acid anhydride group refers to a -CO-O-CO- group obtained by intramolecular dehydration condensation of two molecules of carboxylic acid.
[0084] Examples of the ring structure include an alicyclic structure, a heterocyclic structure, and an aromatic ring structure. Examples of the ring structure include preferably an aromatic ring structure. That is, the acid anhydride monomer is preferably an acid anhydride monomer containing an aromatic ring.
[0085] Examples of the aromatic ring-containing acid anhydride monomer include aromatic ring-containing acid dianhydride and aromatic ring-containing acid tricyanide.
[0086] Examples of the acid dianhydride containing an aromatic ring include pyromellitic dianhydride, bisphenol-type dianhydride (preferably bisphenol A-type dianhydride), ethylene glycol bisanhydrotrimellitate, naphthalene-1,4,5,8-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride.
[0087] As an example of the acid trianhydride containing an aromatic ring, trimellitic anhydride is mentioned.
[0088] As the acid anhydride monomer containing an aromatic ring, preferably, an acid dianhydride containing an aromatic ring can be mentioned. As the acid anhydride monomer containing an aromatic ring, more preferably, pyromellitic dianhydride, bisphenol A type dianhydride, and / or ethylene glycol ditrimellitate anhydride can be mentioned. As the acid anhydride monomer containing an aromatic ring, from the viewpoint of improving the adhesion and heat resistance during low temperature lamination, more preferably, pyromellitic dianhydride can be mentioned.
[0089] The acid anhydride monomers can be used alone or in combination of two or more.
[0090] The molecular weight of the acid anhydride monomer is, for example, 1000 or less, preferably 600 or less, more preferably 400 or less, and for example, 100 or more.
[0091] When the molecular weight of the acid anhydride monomer is not more than the above upper limit, the crosslinking density increases, and the adhesion and heat resistance can be improved.
[0092] The content ratio of the acid anhydride monomer will be described later.
[0093] <Crosslinking agent>
[0094] The cross-linking agent includes an epoxy compound and / or an oxazoline compound.
[0095] Examples of epoxy compounds include bisphenol epoxy resins (e.g., bisphenol A epoxy resins, bisphenol F epoxy resins), Novolac epoxy resins (e.g., phenol Novolac epoxy resins, cresol Novolac epoxy resins), aliphatic epoxy resins, alicyclic epoxy resins, hydrogenated bisphenol epoxy resins, and amine epoxy resins. Examples of epoxy compounds include preferably Novolac epoxy resins. Examples of epoxy compounds include more preferably phenol Novolac epoxy resins.
[0096] As the oxazoline compound, for example, a polymer containing an oxazoline group can be mentioned. As the polymer containing an oxazoline group, for example, a homopolymer of a monomer containing an oxazoline group and a copolymer of a monomer containing an oxazoline group and other monomers copolymerizable with the monomer containing an oxazoline group can be mentioned.
[0097] Examples of the monomer containing an oxazoline group include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and 2-isopropenyl-4,4-dimethyl-2-oxazoline.
[0098] Examples of other monomers copolymerizable with the oxazoline group-containing monomer include alkyl (meth)acrylates, unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid), unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile), unsaturated amides (e.g., (meth)acrylamide), vinyl esters (e.g., vinyl acetate, vinyl propionate), vinyl ethers (e.g., methyl vinyl ether, ethyl vinyl ether), α-olefins (e.g., ethylene, propylene), and unsaturated aromatic monomers (e.g., styrene, α-methylstyrene).
[0099] As the oxazoline compound, preferably, there is mentioned a copolymer of an oxazoline group-containing monomer and another monomer copolymerizable with the oxazoline group-containing monomer. As the oxazoline compound, more preferably, there is mentioned an oxazoline group-containing polystyrene.
[0100] The crosslinking agent preferably contains an epoxy compound or an oxazoline compound, and more preferably contains no oxazoline compound but an epoxy compound from the viewpoint of improving the adhesion and heat resistance during low-temperature lamination.
[0101] The cross-linking agent can be used alone or in combination of two or more.
[0102] The content ratio of the cross-linking agent will be described later.
[0103] <Non-crystalline hydrocarbon polymer>
[0104] From the viewpoint of improving the pot life, the adhesive composition may contain a non-crystalline hydrocarbon polymer as required. The term "non-crystalline" is defined as a property of a compound having a heat of fusion of less than 1 J / g and a Tg of 0°C or less.
[0105] The non-crystalline hydrocarbon polymer is a polymer containing a structural unit derived from a hydrocarbon. As the hydrocarbon, from the viewpoint of improving the adhesion during low-temperature lamination, preferably an olefin having 2 to 20 carbon atoms can be cited. That is, the non-crystalline hydrocarbon polymer is preferably an olefin polymer containing a structural unit derived from an olefin having 2 to 20 carbon atoms. That is, the non-crystalline hydrocarbon polymer is preferably a polymer of an olefin having 2 to 20 carbon atoms.
[0106] As the olefin having 2 to 20 carbon atoms, for example, ethylene, propylene, 1-butene, cis-2-butene, trans-2-butene, isobutylene, 1-pentene, cis-2-pentene, trans-2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, 3-methyl-1-butene, 1-hexene, 2-hexene, 3-hexene, 2,3-dimethyl-2-butene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene can be mentioned. As the olefin having 2 to 20 carbon atoms, preferably, olefin having 2 to 4 carbon atoms can be mentioned. As the olefin having 2 to 20 carbon atoms, more preferably, ethylene, propylene, and / or isobutylene can be mentioned. As the olefin having 2 to 20 carbon atoms, more preferably, ethylene and propylene are used in combination, and isobutylene is used alone. That is, the non-crystalline hydrocarbon polymer is more preferably an ethylene / propylene copolymer and / or polyisobutylene.
[0107] In addition, the type of the structural unit derived from hydrocarbon and the content ratio thereof are selected so that the hydrocarbon-based polymer becomes non-crystalline.
[0108] Specifically, when the structural unit derived from hydrocarbon includes a structural unit derived from ethylene and a structural unit derived from propylene, the content ratio of the structural unit derived from ethylene is, for example, 40 mol% or more, preferably 50 mol% or more, and for example, 80 mol% or less, preferably 60 mol% or less, relative to the total amount of 100 mol% of the structural unit derived from ethylene and the structural unit derived from propylene. In addition, the content ratio of the structural unit derived from propylene is, for example, 20 mol% or more, preferably 40 mol% or more, and for example, 60 mol% or less, preferably 50 mol% or less, relative to the total amount of 100 mol% of the structural unit derived from ethylene and the structural unit derived from propylene.
[0109] When the content ratio of the structural unit derived from ethylene and the content ratio of the structural unit derived from propylene are not less than the above lower limit and not more than the above upper limit, the adhesiveness during low-temperature lamination is excellent.
[0110] The non-crystalline hydrocarbon polymer can be produced by the same method as the method for producing the crystalline α-olefin polymer having 2 to 20 carbon atoms exemplified in the above-mentioned crystalline modified olefin polymer.
[0111] The dynamic viscosity of the non-crystalline hydrocarbon polymer at 200°C is, for example, 1 cSt or more, and, for example, 100,000 cSt or less. In addition, the non-crystalline hydrocarbon polymer can be divided into a non-crystalline hydrocarbon synthetic oil and a non-crystalline hydrocarbon semi-solid resin based on the above dynamic viscosity. In detail, a non-crystalline hydrocarbon polymer having the above dynamic viscosity of 1 cSt or more, preferably 10 cSt or more, more preferably 100 cSt or more, and, for example, 10,000 cSt or less, preferably 1000 cSt or less, and more preferably 500 cSt or less is a non-crystalline hydrocarbon synthetic oil. In addition, a non-crystalline hydrocarbon polymer having the above dynamic viscosity greater than 10,000 cSt, preferably 30,000 cSt or more, and 100,000 cSt or less, preferably 60,000 cSt or less is a non-crystalline hydrocarbon semi-solid resin.
[0112] When the dynamic viscosity at 200° C. is not less than the above lower limit and not more than the above upper limit, the adhesiveness during low-temperature lamination can be improved.
[0113] In addition, the dynamic viscosity at 200° C. can be measured based on JIS K 2283.
[0114] The weight average molecular weight of the non-crystalline hydrocarbon polymer measured by the GPC method and converted to standard polystyrene is, for example, 5,000 or more, and, for example, 300,000 or less. Specifically, when the non-crystalline hydrocarbon polymer is a non-crystalline hydrocarbon synthetic oil, the weight average molecular weight is, for example, 5,000 or more, preferably 10,000 or more, and, for example, 300,000 or less, preferably 100,000 or less, more preferably 50,000 or less, and further preferably 20,000 or less. When the non-crystalline hydrocarbon polymer is a non-crystalline hydrocarbon semi-solid resin, the weight average molecular weight is, for example, 5,000 or more, preferably 10,000 or more, more preferably 50,000 or more, further preferably 100,000 or more, and further preferably 120,000 or more, and, for example, 300,000 or less, preferably 200,000 or less, and further preferably 160,000 or less.
[0115] The non-crystalline hydrocarbon polymers may be used alone or in combination of two or more.
[0116] The content ratio of the non-crystalline hydrocarbon polymer will be described later.
[0117] <Catalyst>
[0118] The adhesive composition may contain a catalyst from the viewpoint of promoting the crosslinking reaction of the crosslinking agent. Examples of the catalyst include amine catalysts and phosphine catalysts.
[0119] Examples of the amine catalyst include strongly basic tertiary amines. Examples of the strongly basic tertiary amine include 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,6-diazabicyclo[3.4.0]-5-nonene. Preferred amine catalysts include 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU).
[0120] Examples of the phosphine catalyst include tributylphosphine, methyldiphenylphosphine, triphenylphosphine, and phenylphosphine. Preferably, triphenylphosphine is used as the phosphine catalyst.
[0121] As the catalyst, from the viewpoint of improving the adhesion and heat resistance during low-temperature lamination, preferably, an amine catalyst is used.
[0122] The catalyst can be used alone or in combination of two or more.
[0123] The content ratio of the catalyst will be described later.
[0124] <Additives>
[0125] The adhesive composition may contain additives in appropriate proportions as necessary.
[0126] Examples of the additives include leveling agents, defoaming agents, antioxidants, heat stabilizers, ultraviolet absorbers, plasticizers, surfactants, pigments, thixotropic agents, thickeners, tackifiers, surface conditioners, anti-settling agents, weathering agents, pigment dispersants, antistatic agents, fillers, mildew-proof agents, and silane coupling agents.
[0127] The additives may be used alone or in combination of two or more.
[0128] <Preparation of Adhesive Composition>
[0129] In order to prepare the adhesive composition, a crystalline modified olefin polymer, an acid anhydride monomer, a crosslinking agent, a non-crystalline hydrocarbon polymer as required, a catalyst as required, and additives as required are mixed.
[0130] Specifically, first, a crystalline modified olefin polymer and a non-crystalline hydrocarbon polymer are mixed as required to prepare a resin composition. More specifically, a crystalline modified olefin polymer and a non-crystalline hydrocarbon polymer are mixed as required and dissolved in a solvent to prepare a varnish of the resin composition.
[0131] As the solvent, for example, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, alkyl esters, glycol ether esters, ethers and polar aprotic species can be cited. As aliphatic hydrocarbons, for example, n-hexane, n-heptane and octane can be cited. As alicyclic hydrocarbons, for example, cyclohexane and methylcyclohexane can be cited. As aromatic hydrocarbons, for example, toluene and xylene can be cited. As ketones, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone can be cited. As alkyl esters, for example, methyl acetate, ethyl acetate, butyl acetate and isobutyl acetate can be cited. As glycol ether esters, for example, methyl cellosolve acetate, ethyl cellosolve acetate, methyl carbitol acetate, ethyl carbitol acetate, ethylene glycol ethyl ether acetate, propylene glycol methyl ether acetate, 3-methyl-3-methoxybutyl acetate and ethyl 3-ethoxypropionate can be cited. Examples of the ethers include diethyl ether, tetrahydrofuran, and dioxane, and examples of the polar aprotic compounds include N-methylpyrrolidone, dimethylformamide, N,N'-dimethylacetamide, dimethyl sulfoxide, and hexamethylphosphoramide.
[0132] Preferred examples of the solvent include alicyclic hydrocarbons and alkyl esters, and more preferred examples of the solvent include methylcyclohexane and / or ethyl acetate.
[0133] The solvent may be used alone or in combination of two or more. Preferably, methylcyclohexane and ethyl acetate are used in combination as the solvent.
[0134] The blending ratio of the solvent is, for example, 200 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the total amount of the crystalline modified olefin polymer and the optionally blended non-crystalline hydrocarbon polymer.
[0135] The dissolution temperature is, for example, 40° C. or higher, and, for example, 110° C. or lower. The dissolution time is, for example, 1 hour or longer, and, for example, 4 hours or less.
[0136] Thus, a resin composition was prepared.
[0137] The acid value of the resin composition is, for example, 1.00 KOH mg / g or more, preferably 5.00 KOH mg / g or more, and, for example, 20.00 KOH mg / g or less, preferably 15.00 KOH mg / g or less, and more preferably 10.00 KOH mg / g or less.
[0138] In addition, the measuring method of the said acid value is described in detail in the Example mentioned later.
[0139] Next, an acid anhydride monomer, a crosslinking agent, a catalyst as needed, and additives as needed are blended into the resin composition.
[0140] Thus, an adhesive composition (adhesive composition varnish) was prepared.
[0141] The content ratio of the crystalline modified olefin polymer relative to 100 parts by mass of the total amount of the crystalline modified olefin polymer, the acid anhydride monomer and the crosslinking agent is, for example, 70 parts by mass or more, preferably 80 parts by mass or more, more preferably 85 parts by mass or more, and, for example, 95 parts by mass or less.
[0142] In addition, the content ratio of the acid anhydride monomer relative to 100 parts by mass of the total amount of the crystalline modified olefin polymer, the acid anhydride monomer and the cross-linking agent is, for example, 0.1 parts by mass or more, preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, and is 5.0 parts by mass or less, preferably 3.0 parts by mass or less, and more preferably 2.0 parts by mass or less.
[0143] The content ratio of the acid anhydride monomer relative to 100 parts by mass of the crystalline modified olefin polymer is, for example, 0.1 parts by mass or more, preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, and, for example, 5.0 parts by mass or less, preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less.
[0144] The content ratio of the acid anhydride monomer relative to 100 parts by mass of the cross-linking agent is, for example, 1.0 parts by mass or more, preferably 5.0 parts by mass or more, more preferably 10 parts by mass or more, further preferably 15 parts by mass or more, and, for example, 40 parts by mass or less, preferably 30 parts by mass or less, more preferably 25 parts by mass or less.
[0145] The molar ratio of the anhydride monomer to the monomer in the crystalline α-olefin polymer having 2 to 20 carbon atoms (anhydride monomer / monomer) is, for example, 0.5 or more, preferably 1.0 or more, more preferably 2.0 or more, and, for example, 7.0 or less, preferably 6.0 or less, more preferably 5.0 or less.
[0146] In addition, the content ratio of the cross-linking agent relative to the total amount of 100 parts by mass of the crystalline modified olefin polymer, the acid anhydride monomer and the cross-linking agent is, for example, 1.0 parts by mass or more, preferably 5.0 parts by mass or more, more preferably 8.0 parts by mass or more, and, for example, 20 parts by mass or less, preferably 15 parts by mass or less, more preferably 10 parts by mass or less.
[0147] The content ratio of the crosslinking agent relative to 100 parts by mass of the crystalline modified olefin polymer is, for example, 1.0 parts by mass or more, preferably 5.0 parts by mass or more, more preferably 8.0 parts by mass or more, and for example, 30 parts by mass or less, preferably 20 parts by mass or less, more preferably 15 parts by mass or less.
[0148] In addition, when the adhesive composition contains a non-crystalline hydrocarbon polymer, the content ratio of the crystalline modified olefin polymer is, for example, 60 parts by mass or more, preferably 70 parts by mass or more, and for example, 90 parts by mass or less, relative to 100 parts by mass of the total amount of the crystalline modified olefin polymer and the non-crystalline hydrocarbon polymer. In addition, the content ratio of the non-crystalline hydrocarbon polymer is, for example, 10 parts by mass or more, and for example, 40 parts by mass or less, and preferably 30 parts by mass or less, relative to 100 parts by mass of the total amount of the crystalline modified olefin polymer and the non-crystalline hydrocarbon polymer.
[0149] The content of the catalyst relative to 100 parts by mass of the total amount of the crystalline modified olefin polymer, the acid anhydride monomer and the crosslinking agent is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and, for example, 2.0 parts by mass or less, preferably 1.0 parts by mass or less.
[0150] Furthermore, the adhesive composition may be diluted with the above-mentioned solvent during and / or after the above-mentioned preparation.
[0151] When the adhesive composition is diluted, the solid content concentration of the varnish of the adhesive composition is, for example, 10 mass % or more, and for example, 70 mass % or less.
[0152] The acid value of the adhesive composition is, for example, 1.00 KOH mg / g or more, preferably 5.00 KOH mg / g or more, more preferably 10.00 KOH mg / g or more, further preferably 15.00 KOH mg / g or more, and is, for example, 30.00 KOH mg / g or less, preferably 25.00 KOH mg / g or less.
[0153] In addition, the measuring method of the said acid value is described in detail in the Example mentioned later.
[0154] <Effects>
[0155] The adhesive composition contains a crystalline modified olefin polymer, an acid anhydride monomer, and a crosslinking agent. In such an adhesive composition, the crystalline modified olefin polymer, the acid anhydride monomer, and the crosslinking agent undergo a crosslinking reaction to be cured.
[0156] Furthermore, the anhydride monomer has two or more anhydride groups. Therefore, in the cross-linking reaction, the cross-linking density is increased. As a result, the adhesion during low-temperature lamination is improved.
[0157] In addition, the acid anhydride monomer has a ring structure, and as a result, heat resistance is improved.
[0158] The adhesive composition has excellent adhesion and heat resistance during low-temperature lamination, and therefore can be suitably used as an adhesive (dry lamination adhesive) for various components (e.g., electronic components, optical components, and battery components), and can be particularly suitably used as an adhesive for battery case packaging materials.
[0159] In the following description, a laminate including an adhesive layer formed from the above-mentioned adhesive composition, a packaging material including the laminate, and a battery case packaging material including the packaging material are described in detail.
[0160] 2. Laminated body
[0161] Reference Figure 1 One embodiment of the laminated body of the present invention will be described.
[0162] Figure 1 In the figure, the up-down direction on the paper is the up-down direction (thickness direction), the upper side on the paper is the upper side (one side in the thickness direction), and the lower side on the paper is the lower side (the other side in the thickness direction). In addition, the left-right direction and the depth direction on the paper are the plane directions orthogonal to the up-down direction. Specifically, according to the direction arrows in each figure.
[0163] The laminate 10 has a film shape (including a sheet shape) having a predetermined thickness. The laminate 10 extends along a plane direction perpendicular to the thickness direction. The laminate 10 has a flat upper surface and a flat lower surface.
[0164] The laminate 10 includes a first adhesive layer 1 and a substrate 2 in this order on one side in the thickness direction. Specifically, the laminate 10 includes a first adhesive layer 1 and a substrate 2 directly disposed on the upper surface (one surface in the thickness direction) of the first adhesive layer 1.
[0165] The thickness of the laminated body 10 is not particularly limited. The thickness of the laminated body 10 is, for example, 10 μm or more, and for example, 150 μm or less.
[0166] [First Adhesive Layer]
[0167] The first adhesive layer 1 is an adhesive layer for bonding an arbitrary adherend to the substrate 2. The first adhesive layer 1 is formed of an adhesive composition.
[0168] Next, in order to arrange (form) the first adhesive layer 1, although it will be described in detail later, the adhesive composition is applied to the other surface in the thickness direction of the substrate 2, and heated and dried as necessary. Thus, the first adhesive layer 1 is arranged (formed).
[0169] The thickness of the first adhesive layer 1 is, for example, not less than 1 μm, and, for example, not more than 50 μm.
[0170] [Base material]
[0171] The substrate 2 has a film shape (including a sheet shape) having a predetermined thickness.
[0172] The material of the substrate 2 is not particularly limited. As the material of the substrate 2, for example, polymer materials and metal materials can be cited. As the polymer material, for example, olefin resins (for example, polyethylene, polypropylene), acrylic resins, polyester resins, polycarbonate resins, acrylonitrile styrene butadiene copolymer resins (ABS resins), polyamide resins (for example, nylon), and polyphenylene sulfide resins can be cited. As the metal material, for example, aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, and chromium can be cited. In particular, when the laminate 10 is provided with a packaging material 20 (described later), as the material of the substrate 2, a metal material is preferably selected, and aluminum is more preferably selected.
[0173] The thickness of the substrate 2 is not particularly limited. The thickness of the substrate 2 is, for example, 10 μm or more, and for example, 100 μm or less.
[0174] [Manufacturing of Laminated Body]
[0175] Reference Figure 2 A and Figure 2 B One embodiment of a method for producing a laminate will be described.
[0176] The method for producing the laminate 10 includes the following steps: a first step of preparing a substrate 2 ; and a second step of applying an adhesive composition on the other side of the substrate 2 in the thickness direction to arrange (form) a first adhesive layer 1 on the other side of the substrate 2 in the thickness direction.
[0177] In the first step, if Figure 2 As shown in A, a substrate 2 is prepared.
[0178] In the second step, if Figure 2 As shown in B, the first adhesive layer 1 is arranged (formed) on the other surface of the substrate 2 in the thickness direction.
[0179] In order to arrange (form) the first adhesive layer 1 on the other surface of the substrate 2 in the thickness direction, a varnish of an adhesive composition is applied to the other surface of the substrate 2 in the thickness direction.
[0180] In order to apply the varnish of the adhesive composition to the other surface in the thickness direction of the substrate 2 , first, the other surface in the thickness direction of the substrate 2 is subjected to a surface treatment as necessary.
[0181] Examples of the surface treatment include corona treatment, plasma treatment, flame treatment, ozone treatment, primer treatment, glow treatment, and saponification treatment, and preferably, corona treatment is used.
[0182] Next, a varnish of an adhesive composition is applied to the other surface in the thickness direction of the substrate 2 by a known method, and is heated and dried as necessary.
[0183] The heating temperature is, for example, 50° C. or higher, preferably 80° C. or higher, and, for example, 140° C. or lower. The heating time is, for example, 10 seconds or longer, and, for example, 120 seconds or shorter.
[0184] Thus, the first adhesive layer 1 composed of the adhesive composition is disposed (formed) on the other surface in the thickness direction of the substrate 2. In the above manner, the laminate 10 is manufactured.
[0185] Such a laminate 10 includes a first adhesive layer 1 formed of an adhesive composition. Therefore, when the laminate 10 is bonded to an arbitrary adherend via the first adhesive layer 1, the laminate 10 has excellent adhesion and heat resistance during low-temperature lamination.
[0186] 3. Packaging materials
[0187] Reference Figure 3 One embodiment of the packaging material of the present invention will be described.
[0188] The packaging material 20 has a film shape (including a sheet shape) having a predetermined thickness. The packaging material 20 extends along a plane direction perpendicular to the thickness direction. The packaging material 20 has a flat upper surface and a flat lower surface.
[0189] The packaging material 20 includes an inner layer 3 and a laminate 10 (a laminate 10 including a first adhesive layer 1 and a substrate 2 in sequence on one side in the thickness direction) in sequence on one side in the thickness direction. Specifically, the packaging material 20 includes an inner layer 3 and a laminate 10 directly disposed on the upper surface (one surface in the thickness direction) of the inner layer 3.
[0190] The thickness of the packaging material 20 is not particularly limited. The thickness of the packaging material 20 is, for example, 15 μm or more, and for example, 300 μm or less.
[0191] [Inner layer]
[0192] The inner layer 3 is a layer that becomes the inner side when the packaging material 20 is formed into a bag shape.
[0193] When the packaging material 20 is formed into a bag, the material of the inner layer 3 can be appropriately selected according to the presence or absence of heat sealability and the type of the content contained in the bag. Although described in detail later, when the content is an electrolyte, a polyolefin film is selected.
[0194] The thickness of the inner layer 3 is not particularly limited. The thickness of the inner layer 3 is, for example, 10 μm or more and, for example, 600 μm or less.
[0195] [Manufacture of packaging materials]
[0196] In order to manufacture the packaging material 20, the inner layer 3 is arranged on the other side of the laminate 10 in the thickness direction (the other side of the first adhesive layer 1 in the thickness direction), and the first adhesive layer 1 is aged. Thus, the first adhesive layer 1 is cured, and the inner layer 3 is bonded to the laminate 10. In the above manner, the packaging material 20 is manufactured.
[0197] Since the packaging material 20 includes the laminate 10, the aging temperature is low, specifically, 20°C or higher, preferably 40°C or higher, and for example, 80°C or lower. The aging time is, for example, 1 day or longer, and for example, 7 days or less, and preferably 5 days or less.
[0198] The packaging material 20 includes the laminate 10. Therefore, it is excellent in adhesion and heat resistance during low-temperature lamination.
[0199] 4. Battery case packaging materials and batteries
[0200] Reference Figure 4 An embodiment of the battery case packaging material and a battery using the battery case packaging material of the present invention will be described.
[0201] The battery 30 includes a battery case packaging material 31 and an electrolyte 32 packaged in the battery case packaging material 31. The battery 30 also includes a positive electrode 33, a negative electrode 34, and a separator 35 housed in the battery case packaging material 31.
[0202] [Battery case packaging materials]
[0203] The battery case packaging material 31 is formed in a bag shape so that the inner layer 3 in the battery case packaging material 31 is in contact with the electrolyte 32. Specifically, the battery case packaging material 31 packages the electrolyte 32 so that the inner layer 3 is in contact with the electrolyte 32.
[0204] Battery case packaging material 31 such as Figure 4 As shown in the enlarged view of A in FIG, the packaging material 20 (the packaging material 20 having the inner layer 3, the first adhesive layer 1 and the substrate 2 in sequence on the side facing the thickness direction), the second adhesive layer 4, and the outer layer 5 are sequentially provided on the side facing the thickness direction. Specifically, the battery case packaging material 31 comprises the packaging material 20, the second adhesive layer 4 directly disposed on the upper surface (one surface in the thickness direction) of the packaging material 20, and the outer layer 5 directly disposed on the upper surface (one surface in the thickness direction) of the second adhesive layer 4.
[0205] As described above, the packaging material 20 has an inner layer 3, a first adhesive layer 1 and a substrate 2 in sequence on one side in the thickness direction. In the battery case packaging material 31, from the viewpoint of chemical resistance (electrolyte resistance) relative to the electrolyte 32, the inner layer 3 selects a polyolefin film. As a polyolefin film, for example, a polyethylene film and a polypropylene film can be cited. As a polyethylene film, for example, a low-density polyethylene film (LDPE) and a linear low-density polyethylene film (LLDPE) can be cited. As a polypropylene film, for example, a stretched polypropylene film (CPP film), a uniaxially stretched polypropylene film, and a biaxially stretched polypropylene film (OPP film) can be cited. As a polyolefin film, preferably a polypropylene film can be cited. As a polyolefin film, more preferably a stretched polypropylene film (CPP film) can be cited.
[0206] In the battery case packaging material 31, a metal material is preferably used as a material for the base material 2. A more preferred material for the base material 2 is aluminum.
[0207] The second adhesive layer 4 is formed of a known adhesive. Alternatively, the above-mentioned adhesive composition may be used instead of the known adhesive.
[0208] The thickness of the second adhesive layer 4 is not particularly limited. The thickness of the inner layer 3 is, for example, 1 μm or more and, for example, 50 μm or less.
[0209] The outer layer 5 is a layer that becomes the outer side of the battery case packaging material 31 .
[0210] As the material of the outer layer 5, for example, the polymer materials exemplified in the above-mentioned substrate 2 can be cited, preferably, a polyamide resin can be cited, and more preferably, nylon can be cited.
[0211] The thickness of the outer layer 5 is not particularly limited. The thickness of the outer layer 5 is, for example, 10 μm or more, and for example, 100 μm or less.
[0212] The battery case packaging material 31 can be produced by disposing the outer layer 5 on one surface of the packaging material 20 in the thickness direction (one surface of the substrate 2 in the thickness direction) via the second adhesive layer 4 formed by coating a known adhesive (or adhesive composition).
[0213] The battery case packaging material 31 includes the packaging material 20. Therefore, it is excellent in adhesion and heat resistance during low-temperature lamination.
[0214] in addition, Figure 4 In the process, both ends (the inner layers 3 facing each other) of the battery case packaging material 31 are sealed by heat sealing, thereby forming a bag shape.
[0215] [Electrolyte]
[0216] The electrolyte solution 32 is not particularly limited, and contains, for example, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and a lithium salt such as lithium hexafluorophosphate.
[0217] The positive electrode 33 and the negative electrode 34 are disposed facing each other with a gap therebetween so as to be in contact with the electrolyte 32. The separator 35 is disposed so as to be sandwiched between the positive electrode 33 and the negative electrode 34.
[0218] The battery 30 described above can be used as, for example, a lithium ion secondary battery. In such a case, the battery case packaging material 31 can be used as a lithium ion secondary battery case packaging material.
[0219] Example
[0220] Next, the present invention is described based on examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that, unless otherwise specified, "parts" and "%" are based on mass. In addition, the specific numerical values of the mixing ratio (containing ratio), physical property values, parameters, etc. used in the following description can be replaced by the upper limit value (numerical value defined in the form of "below", "less than") or the lower limit value (numerical value defined in the form of "above", "greater than") of the corresponding mixing ratio (containing ratio), physical property values, parameters, etc. recorded in the above-mentioned "specific implementation method".
[0221] <Details of ingredients>
[0222] The trade names and abbreviations of the components used in each Production Example, each Example, and each Comparative Example are described in detail.
[0223] OPPANOL B12SFN: non-crystalline hydrocarbon polymer, polyisobutylene, weight average molecular weight: 76,000, dynamic viscosity at 200°C measured according to JIS K 2283: 37,000 cSt, manufactured by BASF
[0224] PMDA: pyromellitic dianhydride, molecular weight about 218, manufactured by Tokyo Chemical Industry Co., Ltd.
[0225] BISDA: Bisphenol A dianhydride, molecular weight about 520, manufactured by SABIC
[0226] TMEG-100: Ethylene glycol bis(trimellitic anhydride), molecular weight about 410, manufactured by Shin Nippon Rika Co., Ltd.
[0227] TH: 1,2,3,6-tetrahydrophthalic anhydride, manufactured by New Nippon Rika Co., Ltd.
[0228] jER152: Phenol Novolac type epoxy resin, manufactured by Mitsubishi Chemical Corporation
[0229] RPS-1005: Oxazoline-containing polystyrene, manufactured by Nippon Shokubai Co., Ltd.
[0230] D-170N: Isocyanate compound, manufactured by Mitsui Chemicals, Inc.
[0231] DBU: 1,8-diazabicyclo[5.4.0]undec-7-ene, manufactured by Wako Co., Ltd.
[0232] TPP: triphenylphosphine, manufactured by Wako Co., Ltd.
[0233] <Production of Crystalline Modified Olefin Polymer>
[0234] Production Example 1
[0235] [Production of Crystalline α-Olefin Polymer Having 2 to 20 Carbon Atoms]
[0236] Into a 2-liter autoclave fully purged with nitrogen, 900 ml of hexane and 90 g of 1-butene were placed. Then, 1 mmol of triisobutylaluminum was added, the temperature was raised to 70°C, and propylene was supplied so that the total pressure was 7 kg / cm 2 G, 0.30 mmol of methylaluminoxane and 0.001 mmol of racemic-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride in terms of Zr atom were added, and propylene was continuously supplied to maintain the total pressure at 7 kg / cm 2 G, while polymerizing for 30 minutes. Thus, a propylene / 1-butene copolymer (crystalline α-olefin polymer having 2 to 20 carbon atoms) was produced. After the polymerization, degassing was performed, and the propylene / 1-butene copolymer was recovered in a large amount of methanol and dried under reduced pressure at 110°C for 12 hours.
[0237] The melting point of the propylene / 1-butene copolymer is 78.3°C. The heat of fusion of the propylene / 1-butene copolymer measured in accordance with JIS K7122 is 29.2 J / g. The weight average molecular weight of the propylene / 1-butene copolymer measured by GPC method and converted to standard polystyrene is 330,000. The propylene content of the propylene / 1-butene copolymer is 67.2 mol%. The above content is obtained by 13 Calculated by C-NMR measurement.
[0238] [Production of Crystalline Modified Olefin Polymer]
[0239] 3 kg of propylene / 1-butene copolymer was added to 10 L of toluene, and the temperature was raised to 145° C. under a nitrogen atmosphere to dissolve the propylene / 1-butene copolymer in toluene. Further, 382 g of maleic anhydride as a monomer and 175 g of di-tert-butyl peroxide as a free radical polymerization initiator were supplied thereto under stirring for 4 hours, and then stirred at 145° C. for 2 hours. Thus, a maleic anhydride-modified propylene / 1-butene copolymer was produced. Then, it was cooled, a large amount of acetone was added, and the maleic anhydride-modified propylene / 1-butene copolymer was precipitated, and then filtered, washed with acetone, and vacuum dried.
[0240] The melting point of the maleic anhydride modified propylene / 1-butene copolymer is 75.8°C. The heat of fusion of the maleic anhydride modified propylene / 1-butene copolymer measured in accordance with JIS K7122 is 28.6 J / g. The weight average molecular weight of the maleic anhydride modified propylene / 1-butene copolymer measured by GPC method and converted to standard polystyrene is 100,000. In the maleic anhydride modified propylene / 1-butene copolymer, the modification amount (introduction amount) of the monomer is 1% by mass. The above modification amount is obtained by 1 Determined by H-NMR measurement.
[0241] <Production of Non-Crystallizable Hydrocarbon Polymer>
[0242] Production Example 2
[0243] In a continuous polymerization reactor equipped with stirring blades and fully purged with nitrogen, 1 liter of dehydrated and purified hexane was added, and ethylaluminum sesquichloride (Al(C2H5)) adjusted to 96 mmol / L was continuously supplied at a rate of 500 ml / hour. 1.5 ·Cl 1.5 ) hexane solution for 1 hour. Then, VO(OC2H5)C adjusted to 16 mmol / l as a catalyst was continuously supplied. l2 Hexane solution (in an amount of 500 ml / hour) and hexane (in an amount of 500 ml / hour). On the other hand, the polymerization liquid is continuously extracted from the upper part of the polymerization vessel in such a way that the polymerization liquid in the polymerization vessel is always 1 liter. Next, ethylene gas (in an amount of 47 L / hour), propylene gas (in an amount of 47 L / hour), and hydrogen (in an amount of 20 L / hour) are supplied using a bubbling tube. The copolymerization reaction is carried out at 35°C by circulating the refrigerant in a jacket installed outside the polymerization vessel. The obtained polymerization solution is deashed with hydrochloric acid, put into a large amount of methanol, and after precipitation, it is dried under reduced pressure at 130°C for 24 hours. Thus, ethylene / propylene copolymers are manufactured.
[0244] The ethylene content of the ethylene / propylene copolymer was 55.9 mol%. 13The weight average molecular weight of the ethylene / propylene copolymer was 14000. The dynamic viscosity of the ethylene / propylene copolymer at 200° C. measured in accordance with JIS K 2283 was 132 cSt.
[0245] <Preparation of Adhesive Composition>
[0246] Example 1
[0247] [Preparation of resin composition]
[0248] In a flask equipped with a stirring blade and equipped with a Dean Stark device, 100 parts by mass of the crystalline modified olefin polymer of Manufacturing Example 1 and 320 parts by mass of methylcyclohexane were mixed and stirred for 3 hours under reflux conditions to dissolve the crystalline modified olefin polymer of Manufacturing Example 1. Then, the mixture was cooled to 60°C and then 80 parts by mass of ethyl acetate were mixed. Thus, a varnish of a resin composition (solid content concentration of 20% by mass) was prepared. The acid value of the resin composition was 7.5 KOHmg / g.
[0249] [Preparation of Adhesive Composition]
[0250] 100 parts by mass of a resin composition, an anhydride monomer (50 parts by mass of a solution obtained by dissolving 0.3 parts by mass of PMDA in 49.7 parts by mass of ethyl acetate), a crosslinking agent (50 parts by mass of a solution obtained by dissolving 10 parts by mass of jER152 in 40 parts by mass of ethyl acetate), and a catalyst (8.0 parts by mass of a solution obtained by dissolving 0.8 parts by mass of DBU in 7.2 parts by mass of ethyl acetate) were mixed to prepare an adhesive composition.
[0251] Examples 2 to 8 and Comparative Examples 1 to 3
[0252] The adhesive composition was prepared based on the same procedure as in Example 1. However, in Examples 5 and 6, in the preparation of the resin composition, the crystalline modified olefin polymer of Production Example 1, the non-crystalline hydrocarbon polymer of Production Example 2 or Production Example 3, and 320 parts by mass of methylcyclohexane were mixed in a flask equipped with a stirring blade equipped with a Dean Stark device, and stirred for 3 hours under reflux conditions to dissolve them. Then, the mixture was cooled to 60° C., and 80 parts by mass of ethyl acetate was mixed. Thus, the adhesive composition was prepared.
[0253] <Evaluation>
[0254] [Acid value]
[0255] Add 35 ml of toluene and 15 ml of n-butanol to a conical flask, and further add 0.8 g of a diluted solution obtained by diluting 0.1 g of special-grade bromothymol blue with 100 ml of 19% ethanol to prepare a solution. Next, add N / KOH-ethanol solution to the solution until the solution turns green, and then add 5 g of the varnish of the resin composition and the varnish of the adhesive composition of each embodiment and each comparative example respectively to completely dissolve them. Then, titrate the solution with N / KOH-ethanol solution until it turns blue, measure the titration amount, and calculate the acid value based on the following formula (1). The results are shown in Table 1.
[0256] Acid value (KOH mg / g) = (sample titration × factor × 5.61) / sample weight (1)
[0257] In addition, the said sample weight is the weight of the solid content in the varnish of a resin composition.
[0258] [Adhesion during low temperature lamination]
[0259] The adhesive composition of each embodiment and each comparative example is applied to the other side of the aluminum foil as the substrate in the thickness direction, and dried at 120°C for 30 seconds (the dry film thickness is about 3 μm). Thus, the first adhesive layer is configured (formed) on the other side of the aluminum foil in the thickness direction to manufacture a laminate. Next, the other side of the first adhesive layer in the thickness direction is laminated to the corona-treated surface of the CPP film (thickness of 30 μm) as the inner layer on a heating plate at 60°C. Then, aging is performed at 60°C for 3 days. Thus, a packaging material is manufactured.
[0260] The obtained packaging material was cut into a size of 15 mm in width to prepare a test piece. The test piece was subjected to a 180° peel test at a crosshead speed of 50 mm / min at 23°C using a universal tensile tester to measure the peel strength of the aluminum foil / CPP. The results are shown in Table 1. In addition, the adhesion at 23°C was evaluated based on the following criteria. The results are shown in Table 1.
[0261] (Benchmark)
[0262] ◎: The peel strength of aluminum foil / CPP is 11 N / 15 mm or more.
[0263] ○: The peel strength of aluminum foil / CPP is 9 N / 15 mm or more and less than 11 N / 15 mm.
[0264] ×: The peel strength of aluminum foil / CPP is less than 9 N / 15 mm.
[0265] [Heat resistance]
[0266] The above test pieces were subjected to a 180° peel test at a crosshead speed of 50 mm / min at 120°C using a universal tensile tester to measure the heat resistance of the aluminum foil / CPP. In addition, the adhesion at 120°C was evaluated based on the following criteria. The results are shown in Table 1.
[0267] (Benchmark)
[0268] ◎: The peel strength of aluminum foil / CPP is 3N / 15mm or more.
[0269] ○: The peel strength of aluminum foil / CPP is 2 N / 15 mm or more and less than 3 N / 15 mm.
[0270] ×: The peel strength of aluminum foil / CPP is less than 2 N / 15 mm.
[0271] [Applicable period]
[0272] The adhesive composition of each example and comparative example was placed in a 50 cc vial and immersed in a water bath at 25° C. The viscosity 30 minutes after immersion (initial viscosity) and the viscosity 24 hours after immersion were measured, and the viscosity increase ratio was calculated based on the following formula (3).
[0273] Thickening rate (%) = viscosity after 24 hours of immersion / initial viscosity × 100 (3)
[0274] In addition, the pot life was evaluated based on the following criteria. The results are shown in Table 1.
[0275] (Benchmark)
[0276] ◎: The viscosity increase ratio is 105% or less.
[0277] ○: The viscosity increase ratio is greater than 105% and less than 130%.
[0278] ×: The viscosity increase ratio is greater than 130%.
[0279] <Discussion>
[0280] It can be seen that Examples 1 to 8 containing an acid anhydride monomer having a ring structure and two acid anhydride groups have excellent adhesion and heat resistance during low-temperature lamination, compared with Comparative Example 1 containing no acid anhydride monomer and Comparative Example 2 containing an acid anhydride monomer having a ring structure and one acid anhydride group (specifically, TH).
[0281] It is also found that Comparative Example 3 using an isocyanate compound as a crosslinking agent has low heat resistance, whereas Examples 1 to 8 using an epoxy compound or an oxazoline compound as a crosslinking agent have excellent adhesion during low-temperature lamination and excellent heat resistance.
[0282] [Table 1]
[0283]
[0284] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is only for illustration and is not to be construed as limiting. Modifications of the present invention that are obvious to those skilled in the art are included in the appended claims.
[0285] Industrial Applicability
[0286] The adhesive composition, laminate, packaging material, and battery case packaging material of the present invention can be suitably used, for example, in the production of a lithium battery case packaging material.
[0287] Description of Reference Numerals
[0288] 1First adhesive layer
[0289] 2. Substrate
[0290] 3Inner layer
[0291] 4. Second adhesive layer
[0292] 5 Outer Layer
[0293] 10 Laminated body
[0294] 20 Packaging Materials
[0295] 31. Battery casing packaging materials
Claims
1. A bonding composition comprising: Crystalline modified olefin polymers, Anhydride monomers, and Crosslinking agent, The crystalline modified olefin polymer is formed by modifying a crystalline α-olefin polymer having 2 to 20 carbon atoms with a monomer having a functional group that can react with an epoxy group or an oxazoline group. The acid anhydride monomer has a ring structure and two or more acid anhydride groups, The cross-linking agent includes an epoxy compound and / or an oxazoline compound. 2 . The adhesive composition according to claim 1 , further comprising a non-crystalline hydrocarbon polymer having a dynamic viscosity at 200° C. of 1 cSt to 100,000 cSt. 3 .
3. The adhesive composition according to claim 2, wherein The non-crystalline hydrocarbon polymer is a polymer of an olefin having 2 to 20 carbon atoms. The bonding composition according to claim 1 , further comprising a catalyst.
5. The adhesive composition according to claim 4, wherein The catalyst is an amine catalyst.
6. The adhesive composition according to claim 1, wherein The functional group is an acid anhydride group. 7 . A laminate comprising, on one side in a thickness direction, a first adhesive layer formed from the adhesive composition according to claim 1 and a substrate in this order.
8. A packaging material comprising an inner layer and the laminate according to claim 7 in this order on one side in a thickness direction.
9. A battery case packaging material comprising, on one side in a thickness direction, the packaging material according to claim 8, a second adhesive layer, and an outer layer in this order.
Citation Information
Patent Citations
Propylene copolymer, polypropylene composition, use thereof, transition metal compounds, and catalysts for olefin polymerization
WO2004087775A1
Polyolefin adhesive composition
WO2018030050A1